Portaria PRR5 nº 60, de 19 de março de 2019 - Marcelo Alves Dias de Souza (DOU, Brasília, DF, 21 mar. 2019, Seção 2, p. 61., 2019)
Dispensa e designação de servidores para o exercício de função comissionada.